2017
DOI: 10.1007/s12350-016-0452-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Aminophylline and caffeine for reversal of adverse symptoms associated with regadenoson SPECT MPI

Abstract: IV aminophylline and IV caffeine provide rapid, safe reversal of regadenoson-induced adverse effects during SPECT MPI. Oral caffeine appeared similarly effective for CR but not for the combined CR + PRE. Our results suggest PO caffeine may be an effective initial strategy for reversal of regadenoson, but IV aminophylline or IV caffeine should be available to optimize symptom reversal as needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…As regadenoson has an affinity to the A2a receptor &7 times that of caffeine, one can divide the &152 times greater number of molecules of caffeine available than regadenoson, yielding the equivalent of &22 times more molecules. This is consistent with the substantial reversal of symptoms observed by Doran et al 1 Oral caffeine was the third agent evaluated by Doran et al; 1 however, ingested dosages were not accurately measured. Blanchard et al 11 found that a 5 mg/kg oral dose of caffeine (350 mg for a 70 kg person) was absorbed as rapidly with comparable bioavailability compared to a IV caffeine infusion of 210 mg caffeine infused over 30 minutes.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…As regadenoson has an affinity to the A2a receptor &7 times that of caffeine, one can divide the &152 times greater number of molecules of caffeine available than regadenoson, yielding the equivalent of &22 times more molecules. This is consistent with the substantial reversal of symptoms observed by Doran et al 1 Oral caffeine was the third agent evaluated by Doran et al; 1 however, ingested dosages were not accurately measured. Blanchard et al 11 found that a 5 mg/kg oral dose of caffeine (350 mg for a 70 kg person) was absorbed as rapidly with comparable bioavailability compared to a IV caffeine infusion of 210 mg caffeine infused over 30 minutes.…”
supporting
confidence: 81%
“…13 Doran et al used a low threshold for reversal in their study, reversing 63% of patients. 1 Most labs choose a higher threshold and reverse a much lower percentage of patients. If a patient is reversed, we recommend waiting 3 minutes following radiotracer administration.…”
mentioning
confidence: 99%
“…This agent is administered via either an IV or oral route. Both oral and IV caffeine were recently compared in a randomized controlled fashion to IV aminophylline by Doran et al17 and were shown to provide rapid and safe reversal of vasodilator-induced adverse effects during SPECT MPI. This study evaluated the effect of reversal agents on patient-reported symptoms in a series of 241 consecutive patients presenting to the stress laboratory and undergoing regadenoson stress.…”
Section: Alternative Non-aminophylline Based Vasodilator Stress Revermentioning
confidence: 99%
“…Rates of complete or predominant reversal were 100% with IV aminophylline, 96% with IV caffeine ( P = NS vs aminophylline), and 84% with PO caffeine ( P = 0.003 vs IV aminophylline). Of the 37 patients in the oral caffeine group, 19 assigned to oral caffeine crossed over to receive IV caffeine based on concern the symptoms might be too severe for oral caffeine to be effective 17…”
Section: Alternative Non-aminophylline Based Vasodilator Stress Revermentioning
confidence: 99%
“…16 A recent study investigated the use of IV and oral caffeine as a potential alternative to aminophylline for the reversal of regadenoson-induced adverse effects. 17 The significance of prior caffeine consumption on regadenosoninduced coronary hyperemia and the diagnostic sensitivity of MPI for detection of perfusion abnormalities have been recently debated in the Journal. [18][19][20][21][22] Our view is that moderate caffeine consumption (i.e., B2 cups of coffee more than 1 hour prior to presentation to the stress laboratory) does not alter coronary flow reserve to such an extent to significantly impact myocardial perfusion pattern on MPI.…”
mentioning
confidence: 99%